Peran Literasi Keuangan dan Sikap Terhadap Uang Dalam Meningkatkan Pengelolaan Keuangan UMKM - Sabrina Ainur Haliza; Achmad Wicaksono; Erlyna Tri Rohmiatun; Kafidin Muzakki (Journal of Business and Economics Research (JBE), 2026)
The low quality of financial management remains a major obstacle for MSMEs, particularly in the areas of recording, planning, and controlling business finances. This study aims to analyze the role of financial literacy and attitudes toward money in improving MSME financial management in Tulangan District. This study employs a quantitative approach through descriptive and associative methods. Information was obtained by distributing questionnaires to 97 selected MSMEs using the Slovin technique. The techniques used included data analysis, validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination (R2) testing, and T-tests and F-tests, all aided by SPPS version 27 software. These findings indicate that financial literacy significantly influences MSME financial management with a t-value of 3.876 and a significance level of 0.000. Attitudes toward money significantly influence financial management with a t-value of 3.974 and a significance level of 0.000. Together, these two variables also significantly influence MSME financial management with a significance level of 0.000. The coefficient of determination of 51.3% indicates that both variables can account for most of the variation in financial management. This research provides an empirical contribution to strengthening the application of the Theory of Planned Behavior to MSME financial management by demonstrating that financial literacy and attitudes toward money play a role in improving financial management. These findings can also serve as a reference for MSMEs and policymakers in designing programs to improve their business financial management capacity.